Concept of State based on Pancasila, the 1945 constitution in criminal radicalism - PANJAITAN, M JS (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this article is to analyze the functions of the Pancasila and the 1945 Constitution to fend off radicalism that has developed in Indonesia. This study concludes that the Indonesian government is following its function of fending off radical group movements in two ways, namely taking legal action and preventing them. The establishment of the Khilafah state is contrary to the concept of the Nation-State as built-in Indonesia. Indonesia was proclaimed on August 17, 1945; it was a Nation-State and not a religious State. The agreement of the founding fathers was stated in the 1945 constitution.